Everything you always wanted to know about Lacan : (but were afraid to ask Hitchcock) - Žižek, Slavoj (Verso, 2010)
Hitchcock gets onto the analyst's couch in this extraordinary volume of case studies. The contributors bring to bear an unrivalled enthusiasm and theoretical sweep on the entire Hitchcock oeuvre, from "Rear Window" to "Psycho", which is shown to be an exemplary source of postmodern defamiliarization. Starting from the premise that 'everything has meaning', the authors analyze the films' ostensible narrative content and formal procedures to discover a rich proliferation of ideological and psychic mechanisms at work. But Hitchcock is also a bait to lure the reader into a serious Marxist and Lacanian exploration of the construction of meaning. An extraordinary landmark in Hitchcock studies, this edition features a brand new essay by Slavoj A iA ek.